2010
DOI: 10.1242/dev.039487
|View full text |Cite
|
Sign up to set email alerts
|

Maternal control of early mouse development

Abstract: The hiatus between oocyte and embryonic gene transcription dictates a role for stored maternal factors in early mammalian development. Encoded by maternal-effect genes, these factors accumulate during oogenesis and enable the activation of the embryonic genome, the subsequent cleavage stages of embryogenesis and the initial establishment of embryonic cell lineages. Recent studies in mice have yielded new findings on the role of maternally provided proteins and multi-component complexes in preimplantation devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
317
0
13

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 390 publications
(345 citation statements)
references
References 120 publications
9
317
0
13
Order By: Relevance
“…Esto sugiere que la IVM modifica el microambiente del ovocito, al ocasionar un cambio celular y genético que impide que esta célula se desarrolle de manera normal (10) . Desde folículo primordial hasta el folículo preantral, el ovocito almacena transcritos (11) , cuya traducción genera proteínas que son claves para su maduración (12) y, después de ser fertilizado, para su transición hacia el embrión (13) .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Esto sugiere que la IVM modifica el microambiente del ovocito, al ocasionar un cambio celular y genético que impide que esta célula se desarrolle de manera normal (10) . Desde folículo primordial hasta el folículo preantral, el ovocito almacena transcritos (11) , cuya traducción genera proteínas que son claves para su maduración (12) y, después de ser fertilizado, para su transición hacia el embrión (13) .…”
Section: Introductionunclassified
“…This suggests that the IVM modifies the microenvironment of the oocyte, to cause cellular and genetic change that prevents this cell to develop as normal (10) . From primordial follicle until the preantral follicle the oocyte stores transcripts (11) , whose translation produces proteins that are key to its maturation (12) and, after being fertilized, for its transition to the embryo (13) .…”
Section: Introductionmentioning
confidence: 99%
“…Preimplantation development is regulated by the synergic action of cytoplasmic and nuclear determinants inherited by the egg and acquired during the oocyte growth: mRNAs, small interfering RNAs (siRNAs) and transcription factors are all required to regulate the expression of the female genome during these early stages. When the expression of one of the 27 maternal-effect factors identified so far is altered, mouse embryos arrest development, mostly at the 2-cell stage (for a review see [13]). We have recently shown that one of the possible causes of the developmental incompetence of MII NSN oocytes is the down-regulation of two maternaleffect factors, OCT4 and STELLA [27,28], required for development beyond the 2-cell stage [8,20].…”
Section: Introductionmentioning
confidence: 99%
“…11 Proteins are also targeted for degradation during early development through the ubiquitinproteasome pathway and macroautophagy (see reviews 12,13 ).…”
mentioning
confidence: 99%